Dose-dependent white matter damage after brain radiotherapy. Issue 2 (November 2016) - Connor, Michael; Karunamuni, Roshan; McDonald, Carrie; White, Nathan; Pettersson, Niclas; Moiseenko, Vitali; Seibert, Tyler; Marshall, Deborah; Cervino, Laura; Bartsch, Hauke; Kuperman, Joshua; Murzin, Vyacheslav; et al.
Abstract: Background and purpose: Brain radiotherapy is limited in part by damage to white matter, contributing to neurocognitive decline. We utilized diffusion tensor imaging (DTI) with multiple b -values (diffusion weightings) to model the dose-dependency and time course of radiation effects on white matter. Materials and methods: Fifteen patients with high-grade gliomas treated with radiotherapy and chemotherapy underwent MRI with DTI prior to radiotherapy, and after months 1, 4–6, and 9–11. Diffusion tensors were calculated using three weightings (high, standard, and low b -values) and maps of fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity ( λ ∥ ), and radial diffusivity ( λ ⊥ ) were generated. The region of interest was all white matter. Results: MD, λ ∥, and λ ⊥ increased significantly with time and dose, with corresponding decrease in FA. Greater changes were seen at lower b -values, except for FA. Time–dose interactions were highly significant at 4–6 months and beyond ( p  < .001), and the difference in dose response between high and low b -values reached statistical significance at 9–11 months for MD, λ ∥, and λ ⊥ ( p  < .001, p  < .001, p  = .005 respectively) as well as at 4–6 months for λ ∥ ( p  = .04). Conclusions: We detected dose-dependent changes across all doses, even <10 Gy. Greater changes were observed at low b -values, suggesting prominent extracellular changes possibly due to vascular permeability and neuroinflammation.